Design and implementation of continuous finite-time sliding mode control for 2-DOF inertially stabilized platform subject to multiple disturbances - Mao, Jianliang; Li, Shihua; Li, Qi; Yang, Jun (ISA transactions, 2019)
Control performances of inertially stabilized platforms (ISPs) are always affected by various disturbed phenomena such as cross-couplings, mass unbalance, parameter variations, and external disturbances in real applications. To improve the dynamic response and the disturbance rejection ability of the ISP, a continuous finite-time sliding mode control (SMC) approach with cascaded control structure is proposed. By constructing a finite-time disturbance observer, the multiple disturbances are precisely estimated in real time without the complex modeling and calibration work. Under the field oriented control framework, for the stabilized loop subsystem, an improved super-twisting controller incorporating the disturbance estimates is developed whereas for the current loop subsystem, the super-twisting control method is directly employed. Finite-time convergence of the inertial angular rates is guaranteed with the continuous control action such that chattering is alleviated remarkably. Moreover, by utilizing the manner of disturbance compensation, the feedback control gains can be tuning down without sacrificing the disturbance rejection ability. Comparative experiments are performed to verify the effectiveness of the proposed control approach. •Multiple disturbances are estimated and compensated without complex modeling work.•Finite-time convergence of the inertial angular rate tracking error is guaranteed.•Control chattering is alleviated remarkably due to continuous control actions.